PENGARUH PELATIHAN DAN PENGEMBANGAN DAN JABATAN FUNGSIONAL TERHADAP MOTIVASI BERPRESTASI DOSEN PERGURUAN TINGGI SWASTA - Effiyaldi . (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2014)
The Low of lectures achievement motivation at the Private Higher Education (PTS) is the focus of this research. After implemented survey, it is found that 39.7% of training and development activities con-tributed to achievment motivation, whereas contibution of lecturer function is 34 %. According to statistical examination, lecturer functional has more significant influnced on achievment motivation. Hence, lecturer funtional development is one of the strategies to improve achievment motivation. Keywords. Training Â and development, functional positions, and achievment motivation.